Strategic Human Resources Management And Organizational Performance: A Literature Review (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Strategic Human Resources Management is one of the concepts of how HR management should be carried out in the organization. The strategic HRM approach shows how the organization's goals will be achieved through competent individuals through various HR strategies and integrating HR policies and practices. Consequently, HR professionals must understand various activities that have strategic value. However, various studies have shown that human resources have not optimized achieving performance at the organizational level. Various factors become a black box in determining the extent to which HR can contribute strategically. Creativity and innovation, including the ability to act fast and agile, become imperative for an organization to survive. It is all in the hands of employee that exist in the organization. The Covid-19 pandemic event is momentum for all HR professionals to rethink the extent to which the organization's HR system has been strategic.